Pengaruh Bonang Sekaten pada Bonang Barung: Kajian Garap Karawitan - Teguh, Teguh; Widiandari, Widiandari (Institut Seni Indonesia Surakarta, 2021)
Bonang barung is one of the ricikan found in the gamelan sekaten and gamelan ageng. It functions as ricikan garap, it means that bonang barung must work on balungan gending. The techniques or motifs of the wasps include: mipil, gembyang, imbal, and klenangan. Of the several wasps, many of the mipil wasps are adopted from the bonang sekaten wasps. This study aims to determine the relationship between wasp motifs and balungan gending. The method used is descriptive analytical. Data was collected through interviews with several interviewees. In addition to interviews, the literature study was also carried out based on references about musical knowledge and several writings related to the material. The final result of this study shows that there are two things happen because of the effect of bonang sekaten wasp on the bonang barung wasp, namely adoption and adaptation.